STRATEGI BERTAHAN HIDUP PENARIK BECAK DI KELURAHAN DAPU – DAPURA KECAMATAN KENDARI BARAT KOTA KENDARI - Lita Julia Ningsih M Ningsih M; sarlan Adi Jaya (KABANTI : Jurnal Kerabat Antropologi, 2023)
This study aims to determine the survival strategy of rickshaw pullers, Dapu – Dapura village. The theory used is social action put forward by Max Weber. The data collection technique was field research using ethnographic methods of involved observation and in-depth interviews. The data analysis technique used is descriptive qualitative. The results of the study show that (1) The obstacles that are felt by the rickshaw pullers in meeting their daily needs are competition with online modes of transportation, the increasing cost of living and the decreasing physical strength of the rickshaw pullers. (2) The rickshaw puller's survival strategy is to seek additional income (either by looking for a side job or with the help of family members, their wife or children). Making expenditure savings (both in meeting the needs of food (clothing), clothing (clothing), housing (boards), health and family education). As well as asking for help from other people (be it family, relatives or the government).